Promoting Affirmative Transgender Health Care Practice Within Hospitals: An IPE Standardized Patient Simulation for Graduate Health Care Learners - Emily L. McCave (Association of American Medical Colleges, 2019)
Introduction Transgender patients frequently experience discrimination within health care settings due to provider lack of knowledge and bias resulting in poor service delivery. Team-based interprofessional collaboration is becoming a best practice for health professionals to improve patient-centered care and address these health disparities. Methods A team-based interprofessional education simulation activity was developed as a teaching activity at a university for graduate health care learners in medicine, nursing, occupational therapy, physical therapy, physician assistant, social work, and health care administration programs over 2 years (N = 494). The simulation focused on a transgender patient brought to the emergency department (ED) after a workplace assault. Students were placed in interprofessional teams and asked to critique the initial ED interaction with the patient and then complete a team huddle and discharge planning meeting with a standardized patient. Student preparedness to engage in the Interprofessional Education Collaborative (IPEC) competencies was assessed through a posttest measure. Results Student learners reacted overwhelmingly positively to the activities of the workshop. The averaging of 2 years of data yielded students responses of strongly agree and agree at 90% or higher for all IPEC core competencies, as well as for educational objectives of the workshop. Discussion Reducing the structural, interpersonal, and individual stigma experienced by transgender patients requires institutions to offer experiential learning opportunities for future health care providers. This interprofessional education simulation experience focusing on transgender patients calls attention to the negative impact of stigma while also promoting competency in interprofessional practice.